Монгол хэлээр орчуулагдсан италийн уран зохиолын товч тойм: A Brief Survey of Italian Literature Translated into Mongolian - Yu., Munkh-Amgalan (Mongolian Journal of Foreign Languages and Cultures, 2023)
Mongols have a long and rich tradition of translating literary works from many different countries into Mongolian. Specifically, thousands of literary works from over 100 different countries written in dozens of different languages have been translated into Mongolian. Among these, a large number of Italian literary works have been translated into Mongolian from Russian, English, and Romanian. As for the literary genres of these works, they primarily consist of poetry, prose, and plays (including screenplays). Specifically: 1) Poetry: poems (58 works), songs (1), long poems (3); 2) Prose: folktales (33), authored tales (36), short stories (40), traditional jokes (3), novellas (5), framed stories (1), novels (5); 3) Plays (2), and screenplays (1). In addition, works of non-fiction, including stylized biographical sketches, reminiscences, as well as a political philosophical treatise, have been published. Literary works are generally divided into one of the following two different categories depending on whether they have a specific author or not: a) oral folklore; and b) written literature. The following tasks need to be undertaken to properly study Italian literary works which have been translated into Mongolian and published in Mongolia: A complete bibliography of Italian literary works translated into Mongolian must be compiled, All of the Italian originals must be located and correctly identified, The Russian, English, and Romanian intermediate translations must also be found and carefully consulted, If a work has been translated multiple times by a single translator, the multiple translations must be compared with each other and studied, If a work has been translated multiple times by different translators, the multiple translations must likewise be compared with each other and studied, The Italian originals of poems, songs, tales, and short stories which have been translated into Mongolian should be located and juxtaposed with their translations and published in book format for teaching and research purposes.